2016
DOI: 10.1007/s12020-016-1134-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk of macrosomia remains glucose-dependent in a cohort of women with pregestational type 1 diabetes and good glycemic control

Abstract: Macrosomia risk remains high in type 1 diabetes (T1DM) complicated pregnancies. A linear relationship between macrosomia risk and glycated hemoglobin A1c (HbA1c) was described; however, low range of HbA1c has not been studied. We aimed to identify risk factors and examine the impact of HbA1c on the occurrence of macrosomia in newborns of T1DM women from a cohort with good glycemic control. In this observational retrospective one-center study we analyzed records of 510 consecutive T1DM pregnancies (1998–2012). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
4
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 27 publications
4
36
4
4
Order By: Relevance
“…Additionally, adult women with pregestational diabetes may have cesarean delivery rates as high as 40% and preterm delivery rates as high as 38%, higher than that demonstrated by adolescents in our study. Lastly, fetal weight > 4000 g has been shown to occur in approximately one‐quarter of adult women with pregestational diabetes—higher than our sample, but adolescent pregnancies often have a lower birthweight than adults.…”
Section: Discussioncontrasting
confidence: 59%
“…Additionally, adult women with pregestational diabetes may have cesarean delivery rates as high as 40% and preterm delivery rates as high as 38%, higher than that demonstrated by adolescents in our study. Lastly, fetal weight > 4000 g has been shown to occur in approximately one‐quarter of adult women with pregestational diabetes—higher than our sample, but adolescent pregnancies often have a lower birthweight than adults.…”
Section: Discussioncontrasting
confidence: 59%
“…Recent retrospective data demonstrated that a mean A1C ≥6.0% in pregnant women with type 2 diabetes was associated with increased risk of neonatal complications (preterm birth, neonatal intensive care unit [NICU] admission, neonatal hypoglycemia and jaundice) compared to women with an A1C <6.0% (82). In women with type 1 diabetes and good glycemic control during pregnancy with an A1C of 4.5% to 7.0%, there is still a linear relationship between third trimester A1C and risk of macrosomia (83).…”
Section: Targets Of Glycemic Controlmentioning
confidence: 99%
“…Type 2 DM is increasingly recognised as an important risk factor for poor pregnancy outcomes and is becoming more common. Diabetes type for women giving birth between 2007 and 2017 was type 2 for 12 787 participant women and type 1 for 23 664 participant women; thus, more than one in three women had type 2 DM . The comparable numbers of participant women with type 1 and type 2 DM were 15 407 and 1662 for publications about births between 1987 and 2006; thus in this earlier era, fewer than one in ten women with diabetes were reported as having type 2 .…”
Section: Resultsmentioning
confidence: 95%
“…Many report between 51%and 77% of women delivered via CS, most of whom (71%) had type 1 DM. Fewer papers report lower CS rates: between 36% (both studies of women with type 2 DM) and 49% where the latter paper and one other did not specify diabetes type . Among study settings with lower CS rates (36–49%), type 1 DM accounted for the majority (93%) of a specified type of PPDM.…”
Section: Resultsmentioning
confidence: 95%